THE TAX CONTROL AS A COMPONENT OF TAX ADMINISTRATION - Zhuk О.I. (The actual problems of regional economy development, 2017)
In the article the features of tax control in the system of taxes administration were investigated. The basic approaches to the determination of tax control were defined. Principles of tax control that must be kept were defined and it will ensure efficiency and effectiveness of tax control. Basic forms of tax control were characterized. An advantages of horizontal monitoring that is one of the form of tax controls were directed.